Circulating RNAs in prostate cancer patients. (1st January 2022) - Mugoni, Vera; Ciani, Yari; Nardella, Caterina; Demichelis, Francesca
Abstract: Growing bodies of evidence have demonstrated that the identification of prostate cancer (PCa) biomarkers in the patients' blood and urine may remarkably improve PCa diagnosis and progression monitoring. Among diverse cancer–derived circulating materials, extracellular RNA molecules (exRNAs) represent a compelling component to investigate cancer-related alterations. Once outside the intracellular environment, exRNAs circulate in biofluids either in association with protein complexes or encapsulated inside extracellular vesicles (EVs). Notably, EV-associated RNAs (EV-RNAs) were used for the development of several assays (such as the FDA-approved Progensa Prostate Cancer Antigen 3 (PCA3 test) aiming at improving early PCa detection. EV-RNAs encompass a mixture of species, including small non-coding RNAs (e.g. miRNA and circRNA), lncRNAs and mRNAs. Several methods have been proposed to isolate EVs and relevant RNAs, and to perform RNA-Seq studies to identify potential cancer biomarkers. However, EVs in the circulation of a cancer patient include a multitude of diverse populations that are released by both cancer and normal cells from different tissues, thereby leading to a heterogeneous EV-RNA-associated transcriptional signal. Decrypting the complexity of such a composite signal is nowadays the major challenge faced in the identification of specific tumor-associated RNAs. Multiple deconvolution algorithms have been proposed so far to infer the enrichment of cancer-specific signals from gene expression data. However, novel strategies for EVs sorting and sequencing of RNA associated to single EVs populations will remarkably facilitate the identification of cancer-related molecules. Altogether, the studies summarized here demonstrate the high potential of using EV-RNA biomarkers in PCa and highlight the urgent need of improving technologies and computational approaches to characterize specific EVs populations and their relevant RNA cargo. Highlights: Extracellular RNA molecules (exRNAs) circulate in biofluids (i.e. urine, blood) either in association with protein complexes or encapsulated inside extracellular vesicles (EVs). Most of the literature reports on EV-associated RNAs (EV-RNAs). EV-associated RNAs (EV-RNAs) encompass a mixture of species including miRNA, circRNA, lncRNAs and mRNAs. EV-RNAs are being investigated to ultimately identify cancer–associated alterations through liquid biopsies. EV-RNAs isolated from urines, plasma or serum are currently studied to identify potential prostate cancer biomarkers. Notably, EV-RNAs were already successfully used for the development of several assays (such as the FDA-approved Progensa Prostate Cancer Antigen 3 (PCA3 test)) to improve prostate cancer detection. At the present one of the major challenges in studying EV-RNAs is represented by the fact that circulating EVs in cancer patients include a multitude of diverse populations that are released by both cancer and normal cells from different tissues. The studies summarized here are focused on EV-RNAs species that have already been suggested as potential biomarkers in prostate cancer. Last, we here highlight the urgent need of improving technologies and computational approaches aiming at differentiating specific EVs populations and their relevant RNA cargo.